Persuasive technology : development and implementation of personalized technologies to change attitudes and behaviors : 12th International Conference, PERSUASIVE 2017, Amsterdam, the Netherlands, April 4-6, 2017, Proceedings /: development and implementation of personalized technologies to change attitudes and behaviors : 12th International Conference, PERSUASIVE 2017, Amsterdam, the Netherlands, April 4-6, 2017, Proceedings. (2017) - Unknown
No abstract available